2023
DOI: 10.3390/cells12162059
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel CD26-Targeted Chimeric Antigen Receptor T-Cell Therapy for CD26-Expressing T-Cell Malignancies

Abstract: Chimeric-antigen-receptor (CAR) T-cell therapy for CD19-expressing B-cell malignancies is already widely adopted in clinical practice. On the other hand, the development of CAR-T-cell therapy for T-cell malignancies is in its nascent stage. One of the potential targets is CD26, to which we have developed and evaluated the efficacy and safety of the humanized monoclonal antibody YS110. We generated second (CD28) and third (CD28/4-1BB) generation CD26-targeted CAR-T-cells (CD26-2G/3G) using YS110 as the single-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“… CTCL Preclinical studies [ 34 , 35 ] Regulatory T cells Suicide CD26 Membrane glycoprotein predominantly found on CD4 + T cells, associated with activation/signaling. PTCL Preclinical studies [ 36 ] A variety of normal cells, including those of the digestive system and lungs Suicide CD70 TNF ligand family member, expressed in activated T cells, leukemias, and lymphomas. PTCL Preclinical studies [ 37 ] Activated B cells, T cells Suicide CD276 (B7–H3) B7 family member, expressed in solid tumors and ALCL, linked to immune evasion.…”
Section: Exploration Of Car-t-cell Therapy Targets In T-cell Malignan...mentioning
confidence: 99%
See 1 more Smart Citation
“… CTCL Preclinical studies [ 34 , 35 ] Regulatory T cells Suicide CD26 Membrane glycoprotein predominantly found on CD4 + T cells, associated with activation/signaling. PTCL Preclinical studies [ 36 ] A variety of normal cells, including those of the digestive system and lungs Suicide CD70 TNF ligand family member, expressed in activated T cells, leukemias, and lymphomas. PTCL Preclinical studies [ 37 ] Activated B cells, T cells Suicide CD276 (B7–H3) B7 family member, expressed in solid tumors and ALCL, linked to immune evasion.…”
Section: Exploration Of Car-t-cell Therapy Targets In T-cell Malignan...mentioning
confidence: 99%
“…CD26 is a key membrane surface glycoprotein that is highly expressed, especially in CD4 + T cells, highlighting its importance in antitumor activity, and it has become a promising target for cancer therapy [ 71 ]. Kobayashi et al [ 36 ] developed second-generation CD28 costimulatory domain-containing and third-generation CD26-targeted CAR-T cells (CD26-2G/3G) containing the CD28 and 4-1BB costimulatory domains to explore their potential against PTCL. In vitro experiments revealed that CD26-2G/3G CAR-T cells exhibited significant antitumor activity against the T-cell leukemia cell line HSB2.…”
Section: Exploration Of Car-t-cell Therapy Targets In T-cell Malignan...mentioning
confidence: 99%
“…To circumvent CD7-related fratricide, researchers are also focusing on finding more suitable biological markers to differentiate between malignant, healthy, and therapeutic T cells. Recent studies have investigated the T-cell receptor β-chain constant domains TRBC1 and TRBC2 ( 24 , 59 ), CD1a ( 60 ), CD2 ( 61 ), CD4 ( 62 ), CD5 ( 63 , 64 ), CD21 ( 65 ), CD26 ( 66 ), CD38 ( 67 ), CD99 ( 68 , 69 ), CCR9 ( 70 ), the natural CD7 ligand SECTM-1 ( 71 ), and the dual targeting of CD38 and LMP1 ( 72 ). Shaw et al.…”
Section: T-cell Malignanciesmentioning
confidence: 99%